Characterization of the Core and Caste-Specific Microbiota in the Termite, Reticulitermes flavipes - Benjamino, Jacquelynn; Graf, Joerg (Frontiers in Microbiology, 2016)
The hindgut of the termite Reticulitermes flavipes harbors a complex symbiotic community consisting of protists, bacteria, and archaea. These symbionts aid in the digestion of lignocellulose from the termite’s wood meal. Termite hindguts were sampled and the V4 hyper-variable region of the 16S rRNA gene was sequenced and analyzed from individual termites. The core microbiota of worker termites consisted of 69 OTUs at the 97% identity level, grouped into 16 taxa, and together accounted for 67.05% of the sequences from the bacterial community. The core was dominated by Treponema, which contained 36 different OTUs and accounted for 32% of the sequences, which suggests Treponema spp have an important impact on the overall physiology in the hindgut. Bray-Curtis beta diversity metrics showed that hindgut samples from termites of the same colony were more similar to each other than to samples from other colonies despite possessing a core that accounted for the majority of the sequences. The specific tasks and dietary differences of the termite castes could have an effect on the composition of the microbial community. The hindgut microbiota of termites from the alate castes differed from the worker caste with significantly lower abundances of Treponema and Endomicrobia, which dominated the hindgut microbiota in workers and soldiers. Protist abundances were also quantified in the same samples using qPCR of the 18S rRNA gene. Parabasalia abundances dropped significantly in the winged alates and the Oxymonadida abundances dropped in both alate castes. These data suggest that the changes in diet or overall host physiology affected the protist and bacterial populations in the hindgut. The in-depth bacterial characterization and protist quantification in this study sheds light on the potential community dynamics within the R. flavipes hindgut and identified a large and complex core microbiota in termites obtained from multiple colonies and castes.